Shared Mattresses, Combs, and Residential Sanitation Associated with Pediculosis Capitis in Orphanages - Qoonitah Salsabiil Putri Istanta; Siti Rohani; Chairil Anwar (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Head lice infestation (pediculosis capitis) continues to be a widespread health issue among children, especially in orphanages. Pediculosis capitis often occurs due to sharing personal items and poor residential sanitation conditions. Methods. This study applied an observational analytic design using a cross-sectional approach, conducted across nine orphanages in South Sumatra Province. Independent variables included sharing personal items and residential sanitation factors such as occupancy density, ventilation, lighting, temperature, and humidity, while the dependent variable was pediculosis capitis occurrence. Results. Pediculosis capitis prevalence reached 37.7%. Sharing mattresses (p = 0.038) and combs (p = 0.016) showed a significant association with pediculosis capitis, while sharing bed sheets, blankets, pillows, towels, headscarves, prayer garments, and caps was not significantly associated. In terms of residential sanitation, occupancy density (p = 0.002), ventilation (p < 0.001), and lighting (p < 0.001) were significantly related to the occurrence of pediculosis capitis. Meanwhile, temperature (p = 0.678) and humidity (p = 0.585) did not show a significant relationship. Conclusion. Pediculosis capitis occurrence is linked to sharing certain personal items and various residential sanitation factors.